Methane Production From Different Parts of Corn Stover via a Simple Co-culture of an Anaerobic Fungus and Methanogen - Li, Yuqi; Hou, Zhesheng; Shi, Qicheng; Cheng, Yanfen; Zhu, Weiyun (Frontiers in Bioengineering and Biotechnology, 2020)
To determine ways to improve the utilization of corn stover for methane production, this study investigated the methane production from different parts of corn stover using a simple co-culture of an anaerobic fungus (Pecoramyces sp.) and methanogen (Methanobrevibacter sp.). The simple co-culture was incubated with the stem pith, leaf blade, or stem bark of corn stover (as substrates) at 39°C for 72 h. Results showed that the stem bark had the lowest (P < 0.05) digestibility (38.0% ± 1.36%) and neutral detergent solubles, i.e., cell solubles (31.6% ± 0.45%), and the highest (P < 0.05) lignin content (4.8% ± 0.56%). The leaf blade had a significantly higher methane conversion rate (56.6 ± 0.76 mL/g digested substrate) than the stem pith (49.2 ± 1.60 mL/g digested substrate), even though they showed similar levels of methane production (42.4 ± 1.00 mL and 40.9 ± 1.35 mL, respectively). Both the leaf blade and stem pith of corn stover have the potential to produce methane in a simple co-culture of an anaerobic fungus and methanogen.